Invited Paper: Integration of Flexible AMOLED Displays Using Oxide Semiconductor TFT Backplanes. Issue 1 (June 2014) - Li, Flora; Smits, Edsger; van Leuken, Linda; Haas, de Gerard; Ellis, Tim; van der Steen, Jan‐Laurens; Tripathi, Ashutosh; Myny, Kris; Ameys, Marc; Schols, Sarah; Heremans, Paul; Gelinck, Gerwin
Abstract AMOLED displays using oxide TFTs and high‐quality moisture barrier were fabricated on ultrathin, flexible plastic substrates to give maximum mechanical flexibility. Total display thickness is below 150μm, and repeated rollability at 1 cm roll radius has been demonstrated. Electrical/Mechanical characteristics and reliability of the flexible displays will be presented.